Quality of life, depression and self-perceived burden among geriatric and non-geriatric hemodialysis patients - Oztop, Kenan Evren; Cetin, Ferhat; Genc, Ahmed Bilal; Varim, Ceyhun; Sipahi, Savas (International Journal of Research in Medical Sciences, 2021)
Background: Many hemodialysis patients need support at various levels from their relatives while performing their daily activities. The ‘burden’ of these needs of patients on their relatives and their negative effects on their lives have been shown in the literature. The aim of the study was to evaluate the ‘care burden’ in terms of the patient. Methods: The patient who had received hemodialysis for at least 3 months was included in the study. A patient identification form including demographic data and medical history data was prepared. The Perceived care burden scale, Beck depression scale and WHO Quality of life questionnaire were applied to the patients. Results: A statistically significant positive correlation was found between SPBS and BDI (p<0.001, r=0.820). A statistically significant negative correlation was observed between the perceived care burden and all sub-dimensions of the quality of life scale (p<0.001). The frequency of comorbidity in the geriatric group was higher than non-geriatric group. A statistically significant positive correlation was found between comorbidity and QOL (p<0.001). The median scores of all sub-dimensions of the QOL scale were lower in geriatric group and there were significance differences except environment dimension. Conclusions: The self-perceived burden on caregivers of hemodialysis patients was positively associated with depression and negatively associated with QOL. Decrease in QOL was more pronounced in geriatric patients.